Processing of volcano infrasound using film sound audio post-production techniques to improve signal detection via array processing - Williams, Ross Adrian (2020)
The use of infrasound for the early detection of volcanic events has been shown to be effective over large distances, and unlike visual methods, is not weather dependent. Signals recorded via an infrasound array often have a poor signal to noise ratio, as other sources of infrasound are detected and recorded along with the volcano infrasound. Array processing software does not always detect known volcanic events, in part because of the amount of noise in the infrasound signal. Infrasound monitoring for atmospheric stud- ies: challenges in middle. Resampling the infrasound into the audible range and then applying the acoustic noise reduction techniques of spectral subtraction prior to array processing is shown to improve signal detection of volcanic events. The discussed technique is applicable to any infrasound signal such as infrasound from anthropogenic sources like nuclear testing.